Emergent Web Intelligence: Advanced Information Retrieval - Chbeir, Richard; Badr, Youakim; Abraham, Ajith; Hassanien, Aboul-Ella (Advanced Information and Knowledge Processing,, 2010)
World Wide Web (WWW) provides interlinked hypertext documents (Web pages) that may contain text, images, videos, and other multimedia. WWW is growing at a remarkable rate and finding appropriate information can therefore be challenging. Web information retrieval deals with the search for documents, for information within documents and for metadata about documents, as well as that of searching databases in the WWW. Web information retrieval is an interdisciplinary science and deals with this challenge by exploiting various information technologies and computational intelligence approaches to design the next generation of web-information retrieval technologies. This Volume provides reviews of cutting-edge technologies and insights into various topics related to XML-based and multimedia information access and retrieval under the umbrella of Web Intelligence, it also illustrates how organizations can gain competitive advantages by applying new techniques in real-world scenarios. The 18 chapters are arranged in three parts and have identified several important problem formulations in the area of Web and multimedia information querying, modelling user interactions and advanced information security and access control models. Chapters are authored by reputed scientists in the field and all articles are self-contained to provide the greatest reading flexibility.